1997
DOI: 10.1021/ie960486l
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification Strategies for Multicomponent Polymer Systems. 2. Study of the Interfacial Tension and Morphology of Linear Low-Density Polyethylene/Poly(vinyl chloride) Blends

Abstract: The breaking thread method was used to measure the interfacial tension between linear low-density polyethylene and poly(vinyl chloride) (PVC). The thermal sensitivity of PVC renders this type of study extremely difficult. By choosing a low molecular weight of the PVC that showed Newtonian plateau behavior at low shear rates, using an appropriate temperature, and substantially reducing the thread thickness to accelerate the experiment, the breakup is constrained to occur before severe thermal degradation. In fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Figure 7 shows the comparison between the data for the sample prepared using method A or B. The behavior observed in this figure is quite similar to the one reported by other authors 9,20,22,23,25,34,35 who have observed the lowering of the measured interfacial tension when an effective compatibilizer is added to one component. The interfacial tension first drastically decreases with compatibilizer concentration and then tends to a limiting value.…”
Section: Resultssupporting
confidence: 84%
“…Figure 7 shows the comparison between the data for the sample prepared using method A or B. The behavior observed in this figure is quite similar to the one reported by other authors 9,20,22,23,25,34,35 who have observed the lowering of the measured interfacial tension when an effective compatibilizer is added to one component. The interfacial tension first drastically decreases with compatibilizer concentration and then tends to a limiting value.…”
Section: Resultssupporting
confidence: 84%
“…The approach has been used extensively in our laboratories for both binary and ternary polymer blend systems. [25][26][27][28][29] Determinations of ␥ 12 by this method have shown an ability to predict the level of compatibility in multicomponent polymer systems. The breaking thread method is the source of ␥ 1,2 data in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Lepers et al, 1997;Lepers and Favis, 1999 , where a triblock copolymer of SEBS grafted with maleic anhydride was successfully used to decrease the interfacial tension in a PPrpolyethylene terephthalate blend. Finally, using modifier Ž designs based on acid᎐base considerations, Liang et al 1997Liang et al , . 1999 demonstrated that the LLDPErpolyvinyl chloride in-Ž terfacial tension was decreased when a poly isoprene-4-.…”
Section: Introductionmentioning
confidence: 99%